Low temperature fast curing powder coating and its coating process

CN121610142BActive Publication Date: 2026-10-09ZHEJIANG JUNCHENG INTELLIGENT EQUIPMENT TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511604745.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-05
Publication Date
2026-10-09
Estimated Expiration
2045-11-05

AI Technical Summary

Technical Problem

[0003]中国专利CN102649895A中提出“紫外光-热双重固化”技术,但其应用对象为转印膜保护层,且未针对静电喷涂粉末、复杂金属几何、孔口背阴区的涂覆-固化一致性问题提供解决方案

Benefits of technology

[0017] This invention uses cationic UV-epoxy powder as the film-forming backbone and utilizes a latent catalyst to compound near-infrared absorbing nanoparticles (Cs) in low-doping amounts within the powder.x (WO3, ITO). The process employs a fixed time sequence of NIR pre-curing followed by UV main curing: NIR rapidly melts the powder within the 95-110°C range and triggers latent catalysis, reducing viscosity and promoting the "dark curing" of cationic polymerization to the shaded area; subsequently, 395nm UV completes the main cross-linking, enabling simultaneous curing of the visible area, the aperture, and the shaded area. Through the combined design of materials, energy, and timing, a dense cross-linked network is formed within the low-temperature window, while simultaneously controlling the powder's electrical and photothermal responses to ensure that electrostatic powdering can reach and transform into shaded areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the field of powder coating, and discloses a low-temperature rapid curing powder coating suitable for complex metal geometrical parts and a coating process thereof. The powder coating has a cationic UV-epoxy matrix, and is compounded with a non-antimony type photoacid generator, a microcapsule latent catalyst and a low-content near-infrared absorption nano filler. The process adopts a fixed sequence of near-infrared pre-activation and then UV main curing, realizes rapid surface drying of thick film and consistent curing of orifices and shaded areas at a workpiece temperature of less than or equal to 120 DEG C, and significantly reduces back spraying and tip powder accumulation. The system and process can be popularized to bearing rings, fasteners, hydraulic valve bodies, aluminum-magnesium alloy housings and electronic metal supports and other components with high requirements for low temperature, short process cycle and shadow consistency, and have good industrial adaptability and energy-saving effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of powder coating technology, specifically relating to a low-temperature rapid curing powder coating and its coating process. Background Technology

[0002] As industries such as automotive parts, bicycles and two-wheeled machinery, construction machinery, home appliances and 3C products, and energy storage devices develop towards lightweight, high-speed, and low-energy consumption, metal parts, aluminum-magnesium structural parts, and heat-sensitive components have placed systematic demands on coatings, requiring "low-temperature rapid curing, corrosion resistance, wear resistance, and high coverage (especially in corners and cavities)." Traditional thermosetting powder systems typically rely on curing temperatures above 180-200°C and holding times of more than 10 minutes, which can easily cause softening and dimensional drift in steel parts (such as bearing rings and pins), and are also unsuitable for heat-sensitive substrates (such as solder joint sealants and electronic heat sink housings). To reduce thermal history and shorten process cycles, the industry has attempted to introduce UV-curable powders or photo-thermal dual-curing combinations, but these technologies are mainly concentrated on planar substrates or coating systems.

[0003] Chinese patent CN102649895A proposes a "UV-thermal dual curing" technology, but its application is limited to transfer film protective layers, and it does not provide solutions for the coating-curing consistency issues of electrostatic powder coating, complex metal geometry, and shaded areas around orifices. Existing technologies have significant limitations in the following three aspects: 1) Poor shaded area consistency: Chemical conversion rate, film thickness, and color difference ratio in shaded areas such as cavities, gaps, and threads are significantly reduced compared to the light-exposed surface; 2) Unclear low-temperature curing window and process control: To compensate for insufficient curing, temperatures are often passively increased or insulation is extended, leading to risks to substrate performance and increased energy consumption; 3) Insufficient coupling of materials, powder application, and curing: A complete process scheme is lacking, taking into account the reachability of electrostatic powder application, near-infrared pre-activation, cationic UV curing, low thermal history, and quantitative evaluation indicators.

[0004] In summary, existing technologies either remain purely thermosetting powder systems, which struggle to achieve both surface drying of thick films and edge coverage at low temperatures; or they are photo-thermal dual-curing paint film systems, but lack a complete technical route that matches electrostatic powder spraying, consistency across complex geometries, and industrial mass production processes. Currently, there is a lack of a systematic powder coating technology for multi-metal geometric components (such as pins, sleeves, bearing outer rings, valve bodies, aluminum-magnesium components, electronic metal brackets, etc.) that possesses both good electrostatic powder application performance and rapid surface drying at ≤120°C through a photo-thermal synergistic method, achieving consistent curing in cavities / shaded areas and light-exposed surfaces; and that can achieve high-quality protective coatings for complex structural parts while ensuring stable mass production and energy efficiency. Summary of the Invention

[0005] To solve the above technical problems, achieve consistent curing of complex geometries (orifices, shaded areas) and light-exposed surfaces, and achieve rapid surface drying of thick films, while avoiding tempering and dimensional drift and reducing energy consumption.

[0006] To achieve the above-mentioned technical objectives, the present invention provides the following technical solution.

[0007] A low-temperature rapid-curing powder coating composition, based on a total of 100 parts by weight of cycloaliphatic difunctional epoxy resin and multifunctional low-viscosity epoxy resin, comprises the following components by weight: (a) 40-85 parts of cycloaliphatic difunctional epoxy resin (CAE) and 15-60 parts of multifunctional low-viscosity epoxy resin (mEP); (b) 1.5-3.0 parts of non-antimony photoacid generator (PAG); (c) 0.3-1.5 parts of latent catalyst, wherein the latent catalyst is microencapsulated imidazole salt (MEI) or thermally activated PAG; and (d) 0.25-0.70 parts of near-infrared absorbing nanofiller, containing cesium-doped tungsten bronze (Cs). x (e) 0.05-0.20 parts of WO3 and 0.20-0.50 parts of indium tin oxide (ITO), both with a median particle size D50 of less than 100 nm and modified by silane coupling; (f) 0.5-2.0 parts of leveling agent, 0.3-1.0 parts of wax and 0.1-0.5 parts of defoamer; (c) 1-5 parts of sheet glass and 1-3 parts of zinc phosphate.

[0008] Preferably, the composition by weight is: 60 parts of cycloaliphatic difunctional epoxy resin (CAE), 30 parts of multifunctional low-viscosity epoxy resin (mEP), 2.2 parts of PAG, 0.8 parts of microencapsulated imidazole salt (MEI), and Cs. x WO3 0.12 parts, ITO 0.35 parts, leveling agent 1.0 part, wax 0.8 parts, defoamer 0.3 parts, sheet glass 3.0 parts, zinc phosphate 2.0 parts.

[0009] Preferably, the PAG is a diaryliodoium salt (IOD-PAG) or a sulfonium salt (SUL-PAG), and its anion is tetra(pentafluorophenyl)borate ([B(ArF)4]). - ) or hexafluorophosphate (PF6) - ).

[0010] Preferably, the microencapsulated imidazole salt (MEI) has a capsule particle size D50 of 0.5-5 μm, a trigger temperature of 90-115 °C, and a capsule shell material of acrylate (ACR) or urea-formaldehyde resin (UF).

[0011] Preferably, the Cs x The specific surface area of ​​WO3 and ITO is 10-80 m². 2 / g, and the volume resistivity of the composition is not less than 1×10 12 Ω.cm.

[0012] Preferably, a low-friction functional filler system is composed of 3-6 parts of polytetrafluoroethylene (PTFE) and / or 2-5 parts of tetrafluoroethylene-hexafluoropropylene copolymer (FEP), so that the resulting coating has a dry friction coefficient of 0.12-0.18, a cross-cut adhesion grade of 0-1, and a methyl ethyl ketone (MEK) double-rub cycle of not less than 120 times under the condition of a film thickness of 50-70 μm.

[0013] Preferably, the powder has a bimodal particle size distribution, with Dv as the laser diffraction volume distribution. 50 The volume fraction of particles with a diameter of 25-35 μm and a particle size of less than 10 μm is 10-15%.

[0014] Furthermore, the low-temperature rapid-curing powder coating composition can be applied to the coating of needle roller bearing outer rings, fasteners, hydraulic valve bodies, motor stator laminations, aluminum-magnesium alloy housings, or metal brackets for electronic devices.

[0015] Furthermore, this invention also discloses a coating process for a low-temperature rapid-curing powder coating, comprising the following steps in sequence: S1) Pretreatment: degreasing, sandblasting to achieve a Ra of 2.5-6.3 μm, forming a silane conversion film, and drying at a temperature not exceeding 110°C; S2) Electrostatic spraying: using 70-90 kV for initial spraying and low-voltage close-range finishing spraying at the end, the aforementioned low-temperature rapid-curing powder coating is deposited on the outer circle, end face, and inner edge of the orifice, while the workpiece rotates at 10-20 rpm; S3) Near-infrared (NIR) preheating: at 30-60 kW / m 2 Irradiation treatment for 30-70 seconds to bring the workpiece metal temperature (PMT) to 95-110°C; S4) Ultraviolet (UV) primary curing: with a total dose of 1.0-1.5 J / cm² using a 395nm LED. 2 Irradiation completes the cationic epoxy ring-opening polymerization; S5) Supplemental curing: Curing with hot air at no higher than 115 °C for 1-2 min or supplemental curing with low-power NIR for 30-60 s.

[0016] As a further improvement, the resulting coating meets the following shading and visible light consistency index: (a) FTIR 915 cm -1 (a) The difference in residual peak area is not greater than 10%; (b) The difference in pencil hardness is not greater than 1 grade, and the number of methyl ethyl ketone (MEK) double rubbings at the shaded area of ​​the well opening is not less than 100 times; (c) The film thickness distribution is 50-70 μm on the outer circle and 40-60 μm at the well opening.

[0017] This invention uses cationic UV-epoxy powder as the film-forming backbone and utilizes a latent catalyst to compound near-infrared absorbing nanoparticles (Cs) in low-doping amounts within the powder.x (WO3, ITO). The process employs a fixed time sequence of NIR pre-curing followed by UV main curing: NIR rapidly melts the powder within the 95-110°C range and triggers latent catalysis, reducing viscosity and promoting the "dark curing" of cationic polymerization to the shaded area; subsequently, 395nm UV completes the main cross-linking, enabling simultaneous curing of the visible area, the aperture, and the shaded area. Through the combined design of materials, energy, and timing, a dense cross-linked network is formed within the low-temperature window, while simultaneously controlling the powder's electrical and photothermal responses to ensure that electrostatic powdering can reach and transform into shaded areas.

[0018] Compared with existing technologies, the technical advantages achieved by this invention are: Under low-temperature conditions ≤120 °C, it achieves rapid surface drying of thick films and consistent curing of complex geometries (orifices, shaded areas): a typical performance index is FTIR 915 cm⁻¹. -1 The residual oxygen difference is ≤10%, the orifice film thickness is 40-60μm, and the MEK double-rubbed coating in the shaded areas can withstand ≥100 cycles. The appearance and mechanical properties match those of the visible surface. Simultaneously, it maintains the steel parts from softening and dimensional drift, while shortening the coating time and reducing energy consumption. Compared to purely thermosetting or general photo-thermal dual-curing solutions, this invention features comprehensive improvements in powder formulation, electrostatic powdering, NIR and UV timing, and quantitative evaluation of the film layer, resulting in a stable and highly adhesive, wear-resistant, and corrosion-resistant protective coating for chains. It is suitable for mass production coating of various industrial parts such as bearings, fasteners, valve bodies, and aluminum-magnesium components. Detailed Implementation

[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the protection scope of the present invention.

[0020] 1. Raw materials For ease of understanding, the following terms and abbreviations are used for the compounds: Cycloaliphatic difunctional epoxy resin (CAE); Multifunctional low-viscosity epoxy resin (mEP); Photoacid generator (PAG): Types include diaryliodomonium salts (IOD-PAG) and sulfonium salts (SUL-PAG); the preferred anion is tetra(pentafluorophenyl)borate ([B(ArF)4)). - ) or hexafluorophosphate (PF6) - ); Microencapsulated imidazole salt (MEI); Cesium-doped tungsten bronze (Cs x WO3) nanoparticles, median particle size D 50 <100 nm; Indium tin oxide (ITO) nanoparticles, D 50 <100 nm; Silane coupling agent; Polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP); Fourier transform infrared spectroscopy (FTIR); methyl ethyl ketone (MEK); metal temperature (PMT); near-infrared (NIR); ultraviolet (UV).

[0021] All commercial raw materials are standard industrial grade or analytical grade; NIR nanoparticles (Cs) x Both WO3 and ITO are first treated with Silane coupling surface treatment before use.

[0022] 2. Formula This invention provides a low-temperature rapid-curing powder coating composition, which, based on a total of 100 parts by weight of CAE and mEP, comprises the following components in parts by weight: CAE 40–85 parts, mEP 15–60 parts; PAG 1.5–3.0 parts (IOD-PAG or SUL-PAG, anion [B(ArF)4]) - or PF5 - MEI 0.3-1.5 parts (or thermally activated PAG); near-infrared absorbing nanofiller 0.25-0.70 parts, of which Cs x WO3 0.05-0.20 parts, ITO 0.20-0.50 parts; leveling agent 0.5-2.0 parts, wax 0.3-1.0 parts, defoamer 0.1-0.5 parts; sheet glass 1-5 parts, zinc phosphate 1-3 parts; optional PTFE 3-6 parts and / or FEP 2-5 parts (low-friction functional system).

[0023] Preferred: CAE:mEP = (50-70):(20-40); PAG 2.0-2.4 parts (IOD-PAG preferred); MEI 0.6-1.0 parts; Cs x WO3 0.08-0.15 parts, ITO 0.25-0.40 parts, total NIR nanofiller ≤0.50 parts.

[0024] Powder particle size satisfies the following: the powder has a bimodal particle size distribution, and based on laser diffraction volume distribution, D 50 =25-35μm, and the volume fraction of particles with a diameter <10μm is 10-15%.

[0025] 3. A method for preparing coating powder, comprising the following steps: S1 Premix: Weigh CAE, mEP, PAG, MEI, and Cs according to the formula.x WO3, ITO, additives, and optional PTFE and FEP. High-speed mixer 1000-1500 rpm, 3-5 min.

[0026] S2 melt extrusion: twin-screw extrusion, zone temperature ≤85-90 °C to protect PAG and MEI, screw speed 200-350 rpm.

[0027] S3 Cooling and Crushing: Cold Roller Pressing → Mechanical Crushing.

[0028] S4 classification: Cyclone sieving, target median particle size D 50 =25-35μm.

[0029] S5 Storage: ≤30 °C, <50%RH, protected from light and sealed.

[0030] 4. Coating process Electrostatic spraying: initial stage 70-90 kV, 10-20 μA; final stage low voltage near the spray nozzle; workpiece rotation 10-20 rpm.

[0031] NIR preheating: power density 30-60 kW / m 2 30-70 s, to bring the workpiece PMT to 95-110 °C; UV curing: 395 nm LED, total dose 1.0-1.5 J / cm² 2 If necessary, supplement 0.2-0.4 J / cm² for 365 nm LED. 2 .

[0032] Optional heat supply: ≤115 °C hot air for 1-2 min or low power (e.g., 45kW / m²) 2 NIR 30-60 s.

[0033] Online monitoring: PMT, UV dose, film thickness and defect rate (pinholes / shrinkage / edge shrinkage).

[0034] The curing sequence is NIR first, then UV.

[0035] 4.1 Typical Workpieces and Application Examples To verify the adaptability and industrial scalability of the low-temperature rapid curing powder coating of the present invention on complex metal geometries, typical workpieces were selected as follows.

[0036] Workpiece type: Small and medium-sized steel precision fitting parts, represented by chain pin assemblies, made of 20CrMnTi carburized and quenched steel, also suitable for similar bearing rings, hinge shafts, fasteners and small valve bodies. Workpiece dimensions: diameter φ10 mm, length 45 mm, sleeve inner diameter φ10.1 mm, depth 30 mm; Surface condition: mechanical shot blasting, Sa2.5 grade, roughness Ra 1.6μm; after cleaning, it is treated with cathodic electrophoresis or phosphating film (film thickness 0.8-1.0μm) and then dried for later use.

[0037] Workpiece characteristics: These types of workpieces have typical "difficult-to-cover areas" such as axial orifices, recessed cavities, and the junction area between the outer circle / end face / orifice. At the same time, the metal substrate is sensitive to temperature and is prone to tempering softening or dimensional displacement when the temperature is above 120 °C. They are ideal objects for verifying the consistency and energy-saving performance of the "low-temperature photo-thermal synergistic curing" of this invention.

[0038] Clamping method: The workpiece is fixed by a rotatable hanger with a rotation speed of 10-20 rpm; a double spray gun is arranged in opposite directions (symmetrically positioned 200 mm from the center of the workpiece), and the last spray gun automatically reduces the voltage to 10 kV for additional spraying at the orifice.

[0039] 5. Examples and Comparative Examples 5.1 Formulation and Process Parameters Four examples and four comparative examples of powder coating compositions are given, with the same number of excipients: 1.0 part leveling agent, 0.8 parts wax, 0.3 parts defoamer, 3.0 parts glass flakes, and 2.0 parts zinc phosphate. The differences in formulation are shown in Table 1. The powder coating preparation and coating process are carried out using the above-mentioned methods.

[0040] Table 1. Composition Formulation (parts by weight, phr) The curing dosage for UV395 coating in both the examples and comparative examples was 1.2 ± 0.05 J / cm². 2 The UV365 supplemental heating dose is 0.3 ± 0.02 J / cm². 2 The differences in spraying process parameters are shown in Table 2.

[0041] Table 2 Coating process and particle size parameters 5.2 Test Methods FTIR: 915 cm between the visible surface of the outer circle and the shaded surface of the sleeve orifice. -1 Epoxy residual peak area; results are expressed as residual percentage, difference = shaded - exposed to light.

[0042] Film thickness: magnetic induction / eddy current; the inner edge of the aperture was checked using a section microscopy.

[0043] Hardness: GB / T 6739-2022 Pencil method for determining the hardness of paint film.

[0044] MEK Double Eraser: GB / T 23989-2009.

[0045] Friction coefficient: Pin-on-disk method, GCr15 bearing steel ball grinding, 10 N, 0.2 m / s, 23 °C, 50%RH, report steady-state friction coefficient μ.

[0046] Volume resistivity: GB / T 21788.13-2008 or equivalent test method.

[0047] Color difference ΔE: The color difference between the sample and the standard sample measured under standard light source D65 and standard viewing angle 10°.

[0048] Appearance defect rate: pinholes, shrinkage cavities, and edge shrinkage.

[0049] 5.3 Test Results 5.3.1 The consistency of shadows and visible light between the examples and comparative examples is shown in Table 3.

[0050] Table 3. Consistency between shadows and visible light As shown in Table 3, Examples 1–4 all achieved the target of △≤10% consistency between shadow and visible light; Comparative Examples 1–4 were significantly higher (≥14.7%); the coating hardness and double-rub index of the shadow area of ​​Examples 1–4 were significantly better.

[0051] 5.3.2 The appearance and dimensions of the films in the examples and comparative examples are shown in Table 4.

[0052] Table 4 Film thickness distribution, friction and appearance As can be seen from Table 4, the orifice film thickness of Examples 1–3 increased by 8–14 μm compared to the comparative example, and the outer circle was not too thick; Example 4 shows that after adding PTFE and FEP, the friction coefficient μ significantly decreased to 0.16±0.01, and the consistency was still met.

[0053] 5.3.3 The spraying stability of the examples and comparative examples is shown in Table 5.

[0054] Table 5 Spraying stability As shown in Table 5, increasing ITO or Cs alone... xThe dosage of WO3 (C2, C3) will significantly reduce resistance, increase ΔE and deteriorate spraying stability; low dosage (Examples 1-4) can achieve shading consistency and film thickness improvement while maintaining electrical and color difference indicators.

[0055] The above four examples and four comparative examples demonstrate that, under low PMT and a fixed NIR-UV timing sequence, only low Cs doping... x Only by combining WO3 and ITO with MEI can significant improvements in shaded and visible light areas, FTIR difference ≤10%, and pore film thickness be achieved without increasing temperature and coating dosage, or excessively affecting powder electrical properties and color. The mechanism is that NIR first promotes powder melting and reduces viscosity, triggering low-temperature activation of MEI; subsequently, UV promotes cationic polymerization to continue curing in the shaded area, combined with low Cs doping. x Selective NIR absorption of WO3 and ITO.

[0056] The powder and process conditions of this invention can also be replicated on other metal or composite assemblies, including but not limited to: bearing outer rings, needle roller bushings; aluminum-magnesium alloy housings and electronic brackets; small hydraulic valve bodies and connecting bolts; precision fasteners and sensor brackets. All types of workpieces can use the same NIR→UV sequential curing and PMT ≤ 120 °C process window, with consistent curing achieved by adjusting the spray angle, NIR power density, or lamp array arrangement accordingly.

[0057] It should be understood that the above specific embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. For those skilled in the art, various equivalent substitutions, combinations, adjustments, or modifications can be made based on this without departing from the spirit and essence of the present invention. These include, but are not limited to: substitution of raw material sources and grades, conventional optimization within the dosage range, similar substitution of auxiliary agent systems, engineered adjustment of particle size distribution, process modification of lamp type, power, and dosage, equivalent substitution of pretreatment systems, equivalent substitution of measurement / evaluation methods, and optimization of fixtures and paths for workpieces of different sizes and shapes, all of which fall within the protection scope of the present invention.

Claims

1. A low-temperature, rapid-curing powder coating composition, characterized in that, Based on a total weight of 100 parts by weight of cycloaliphatic difunctional epoxy resin and multifunctional low-viscosity epoxy resin, the following components are composed of parts by weight: (a) 40-85 parts of cycloaliphatic difunctional epoxy resin and 15-60 parts of multifunctional low-viscosity epoxy resin. (b) 1.5-3.0 parts of non-antimony photoacid generator; (c) 0.3-1.5 parts of a latent catalyst, wherein the latent catalyst is a microencapsulated imidazole salt; (d) Near-infrared absorbing nanofiller 0.25-0.70 parts, including 0.05-0.20 parts cesium-doped tungsten bronze and 0.20-0.50 parts indium tin oxide, with a median particle size D 50 All are less than 100 nm and modified by silane coupling; (e) 0.5-2.0 parts leveling agent, 0.3-1.0 parts wax, and 0.1-0.5 parts defoamer; (f) 1-5 parts of sheet glass, 1-3 parts of zinc phosphate; The curing process of the powder coating composition adopts a fixed sequence of NIR pre-curing followed by UV main curing.

2. The powder coating composition according to claim 1, characterized in that, It is composed of the following components in parts by weight: 60 parts of cycloaliphatic difunctional epoxy resin, 30 parts of multifunctional low-viscosity epoxy resin, 2.2 parts of non-antimony photoacid generator, 0.8 parts of microencapsulated imidazole salt, 0.12 parts of cesium-doped tungsten bronze, 0.35 parts of indium tin oxide, 1.0 part of leveling agent, 0.8 parts of wax, 0.3 parts of defoamer, 3 parts of sheet glass, and 2 parts of zinc phosphate.

3. The powder coating composition according to claim 1, characterized in that, The non-antimony photoacid generator is a diaryliodonium salt, whose anion is tetra(pentafluorophenyl)borate or hexafluorophosphate.

4. The powder coating composition according to claim 1, characterized in that, The median particle size D of the microencapsulated imidazole salt capsule 50 The micrometer diameter is 0.5-5 μm, the trigger temperature is 90-115 °C, and the capsule shell material is acrylate or urea-formaldehyde resin.

5. The powder coating composition according to claim 1, characterized in that, The specific surface area of ​​the cesium-doped tungsten bronze and indium tin oxide is 10–80 m². 2 / g, and the volume resistivity of the composition is not less than 1×10 12 Ω.cm.

6. The powder coating composition according to claim 1, characterized in that, Add 3-6 parts of polytetrafluoroethylene and / or 2-5 parts of tetrafluoroethylene-hexafluoropropylene copolymer as a low-friction functional filler system.

7. A coating process for a low-temperature, rapid-curing powder coating, characterized in that, Includes the following steps: S1) Pretreatment: Degreasing, sandblasting to make the surface Ra of the workpiece 2.5-6.3μm, forming a silane conversion film, and drying at no higher than 110 °C; S2) Electrostatic spraying: Using 70-90 kV for initial spraying and low-voltage close-range replenishment spraying at the end, the powder coating composition described in any one of claims 1-6 is deposited on the outer circle, end face and inner edge of the orifice of the workpiece, and the workpiece rotates at 10-20 rpm; S3) Near-infrared preheating: at 30-60 kW / m 2 Irradiation treatment for 30-70 seconds to bring the metal temperature of the workpiece to 95-110 °C; S4) UV curing: 1.0-1.5 J / cm² total LED dose at 395 nm. 2 Irradiation completes the ring-opening polymerization of cationic epoxy; S5) Heat-curing: Curing with hot air at a temperature not exceeding 115°C for 1-2 minutes or with low-power NIR for 30-60 seconds for supplementary curing.

8. The coating process according to claim 7, characterized in that, The resulting coating meets the following consistency index between shadows and visible light: (a) Fourier transform infrared spectrum at 915 cm⁻¹ -1 The difference in residual peak area is no more than 10%; (b) The difference in pencil hardness is no greater than 1 grade, and the number of times the pencil is double-rubbed with methyl ethyl ketone at the shaded area of ​​the hole is no less than 100 times; (c) The film thickness distribution is 50-70 μm on the outer circle and 40-60 μm at the orifice.

9. The powder coating composition according to any one of claims 1-6 is applied to the coating of needle roller bearing outer rings, fasteners, hydraulic valve bodies, motor stator laminations, aluminum-magnesium alloy housings, or metal supports for electronic devices.

Citation Information

Patent Citations

  • Ultraviolet light-heat dual-curing gloss oil, and preparation method and application thereof

    CN102649895A

  • Infrared fast curing weather-resistant powder coating

    CN109321101A

  • Heat-insulating colored coating composition, heat-insulating colored glass and preparation method of heat-insulating colored glass

    CN118546581A